(untitled) (Bangladesh Journal of Anatomy, 2018)
Context: Examination of bone is important for identification of deceased and estimation of sex. The present study was planned to collect data regarding length of manubrium and mesosternum of dry ossified human sternum and to find out possible variations regarding sex. Materials and methods: This was a cross-sectional analytical study, conducted in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2011 to June 2012. The study materials consist of 112 dry ossified human sternum. The length of manubrium and mesosternum was measured and comparison of values between male and female were done. Results: The mean length of manubrium in male and female was 49.92 ± 3.22mm and 40.74 ± 4.19mm respectively and the mean length of mesosternum in male and female was 102.56 ± 6.10mm and 83.44 ± 10.19mm respectively. Conclusion: The length of manubrium and mesosternum was greater in male than that of female which was statistically significant (P < 0.001). The length difference can be useful in sex differentiation. Bangladesh Journal of Anatomy January 2018, Vol. 16, No. 1, pp. 13-16